If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 25y + -6y = 76 Combine like terms: 25y + -6y = 19y 19y = 76 Solving 19y = 76 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '19'. y = 4 Simplifying y = 4
| 2x+4=3(x-7) | | M-200=100 | | 3y-10x=67 | | 55m-4=-6(m+2) | | .8b+1.9=5.5-.4b | | 5(-2+2)=3(-4+6) | | 10=6x-2x-8 | | -35=x-18 | | .8b+1.9=5.5-4b | | 2x+x+30=90 | | -35=x+18 | | 4x+4=-20-2x | | 3/5--2/5= | | 60+p=70 | | 6s-4=-20 | | y=3/4*3+1 | | 4a+1-8a=9 | | 8mn-5m= | | 3l+y=5+5l | | 88-8m=8m+88 | | -16.5h+9.25h=21.75 | | -13y-34y= | | y=3/4(3)+1 | | 2m+3m-6=7m-34 | | 46+y=136 | | 14mn-19mn= | | 3x=7y-2 | | 4y-15y=22 | | 10y^2+28y-5=0 | | -x-45=47 | | 5a^2-17+14=0 | | 9+d=23 |